CRIMINAL RESPONSIBILITY FOR VIOLATION OF TAX DISCIPLINE (World Bulletin of Management and Law, 2024)
The scientific article systematically analyzes the legal foundations of criminal responsibility for tax violations. Meantime, the theoretical aspects of criminal responsibility for tax violations have been tried to clarify. In addition, the meaning of the concept of “criminal responsibility for violation of tax discipline”, a category of responsibilities considered relevant today, is analyzed. The author’s comparative analysis of the legislation of foreign countries served to reflect the unique aspects of the article. Meanwhile, the article puts forward suggestions and recommendations based on the analysis of existing problems in this sphere
Keywords: tax discipline; tax system; offenses; types of taxes